The relationship between the cortisol awakening response and cortisol reactivity to a laboratory stressor. Issue 2 (2nd January 2019) - Dienes, Kimberly; Gartland, Nicola; Ferguson, Eamonn
Abstract : Objectives: The cortisol awakening response (CAR) and cortisol reactivity to an acute laboratory stressor both involve steep increases in cortisol secretion and are associated with preparing the body to deal with stressors ahead. Alterations in both have been linked to negative clinical and health outcomes. However, these two aspects of our biological stress response have rarely been directly compared, and the extant research focuses on state, rather than trait CAR. Given the similar roles of the CAR and cortisol reactivity, and their relationships to psychopathology, it is important to understand whether trait CAR and cortisol reactivity to acute stressors are related and whether a blunted CAR may be predictive of blunted cortisol reactivity across an acute laboratory stress task. Design: Cross‐sectional . Participants completed the Trier Social Stress Test (TSST) the week after daily assessment of the CAR. Methods: Salivary cortisol secretion across the TSST was compared to the CAR, sampled across five weekdays at waking (S1) and 30 min past waking, for 54 female participants. Results: A smaller CAR, lower peak cortisol, and blunted CAR increase were all significantly related to a steep rise and flattened slope of recovery in cortisol secretion following the TSST. Additionally, lower S1 was predictive of a blunted rise in cortisol secretion from baseline to immediately post‐task. Conclusion: There was a significant relationship between trait CAR and cortisol secretion across the TSST. The results provided mixed support for hypotheses. A blunted CAR was associated with impaired recovery in cortisol secretion following the TSST, but, surprisingly, a rapid rise in cortisol peaking immediately following the stress task. Statement of contribution What is already known on this subject? The CAR and cortisol reactivity to an acute laboratory stress task both are thought to marshal the body's resources to deal with stress. Both the CAR and cortisol reactivity have been related to psychosocial states and clinical and health outcomes in past research. State CAR has been linked to cortisol reactivity to stressors, and a greater CAR is thought to help an individual deal with stressors in the day ahead. What does this study add? The current study predicts trait CAR sampled across multiple days from the rise and recovery in cortisol secretion across an acute stress test. Comparison of trait CAR and cortisol reactivity may clarify both their relationship to each other and to clinical and health outcomes.